The final solutions for Common Agricultural Policy in years 2014-2020: Step towards environmental sustainability or business as usual? - Karol Kociszewski (Economic and Environmental Studies (E&ES), 2016)
The Paper's goal is to assess the most important changes in the European Union's Common Agricultural Policy (CAP) for years 2014-2020 in the context of its potential influence on environmental pressure of agriculture. The final solutions of that policy reform were discussed in relation to main groups of instruments: these supporting farmers' incomes and rural development measures. They were analysed in the context of chances and threats for environmental sustainability. The general conclusion is the reform results are far from the initial European Commission's plans as well as far from proposals presented by the NGO's connected with environment protection and organic farming. The CAP financial instruments were not sufficiently directed to the support for sustainable agriculture development.
Keywords: O13; Q1; Q15; Q18; Q5; Q56; Q57; 330; sustainable agriculture and rural development; Sustainable Agriculture; rural development; Common Agricultural Policy; rural development measures